Reduced frequency of knowledge of results enhances learning in persons with Parkinson’s disease - Suzete eChiviacowsky; Tiago eCampos; Marlos Rodrigues Domingues (Frontiers in Psychology, 2010)
Parkinson’s disease (PD) is a progressive neurological disorder, known to cause a large number of motor and non-motor limitations. Research related to factors that affect motor control and learning in people with PD is still relatively limited. The purpose of this study was to compare the effects of different frequencies (100% versus 66%) of knowledge of results (KR) on the learning of a motor skill with spatial demand in participants with PD. Twenty individuals with PD were randomly assigned to one of two groups. The 100% group received KR after each trial, while the 66% group received KR on two thirds of the trials. A linear positioning task with a spatial target was used. Participants carried out the task with the dominant hand while being blindfolded. In the acquisition and retention phases, the goal was to position the cursor at a distance of 60cm from the starting point. The hypothesis was that participants with PD, who practiced with a reduced KR frequency, would demonstrate more effective learning than those who practiced with a 100% KR frequency, similar to previous findings with adults without neurological disorders. The results showed differences between the groups in the retention phase (without KR): The 66% KR group was more accurate and less variable in their performance than the 100% KR group. Thus, reducing the KR frequency can enhance motor learning in persons with PD, similar to what has previously been found for unimpaired participants.